MicroRNAs Expression Profile in MN1-Altered Astroblastoma - Francesca Gianno; Evelina Miele; Claudia Sabato; Elisabetta Ferretti; Simone Minasi; Francesca Romana Buttarelli; Debora Salerno; Natalia Pediconi; Giuseppe Rubens Pascucci; Francesca Guerrieri; Andrea Ciolfi; Simone Pizzi; et al. (Biomedicines, 2025)
Background/Objectives: Astroblastoma is a rare glial neoplasm more frequent in young female patients, with unclear clinical behaviors and outcomes. The diagnostic molecular alteration is a rearrangement of the Meningioma 1 (MN1) gene. MicroRNAs (miRNAs) are important gene expression regulators with strong implications in biological processes. Here, we investigated microRNA expression, regulation, and biological processes correlated to target genes of deregulated miRNAs in MN1-altered astroblastoma. Methods: A cohort of 14 tumor samples, histologically classified as astroblastoma, was retrospectively collected and analyzed through their DNA methylation profiles. MiRNA expression profiles were then detected on MN1-altered astroblastomas (n = 8) and normal brain controls (n = 2) by Nanostring technology and validated by RT-qPCR; then, the expression of deregulated miRNAs was correlated with clinical-pathological characteristics. Subsequently, the methylation status of promoters of deregulated miRNAs was investigated through a methylation profiling microarray. Finally, bioinformatics analysis was conducted to explore the biological processes (BPs) and target genes of differentially expressed miRNAs. Results: Eight MN-altered astroblastoma were identified. Thirty-nine miRNAs were deregulated in tumor samples compared to normal brain tissue. Downregulated microRNAs exhibited an association with an increased risk of recurrence. The promoter methylation status was investigated in 32/39 miRNAs: 14/32 were epigenetically deregulated. None of them were genetically regulated. Conclusions: MN1-altered astroblastomas have an miRNA expression signature that identifies specific BPs and pathways. Our findings suggested that the involved pathways could be associated with clinical and pathological characteristics of MN1-altered astroblastomas. Also, the biology of this rare tumor could have potential implications on prognostic markers and therapy.